2018
DOI: 10.1103/physrevlett.121.045701
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Spinodal Instabilities in the Mott Transition inV2O3: Evidence from Hysteresis Scaling and Dissipative Phase Ordering

Abstract: We present the first systematic observation of scaling of thermal hysteresis with the temperature scanning rate around an abrupt thermodynamic transition in correlated electron systems. We show that the depth of supercooling and superheating in vanadium sesquioxide (V_{2}O_{3}) shifts with the temperature quench rates. The dynamic scaling exponent is close to the mean field prediction of 2/3. These observations, combined with the purely dissipative continuous ordering seen in "quench-and-hold" experiments, ind… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
55
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(62 citation statements)
references
References 79 publications
5
55
2
Order By: Relevance
“…5 (b)] are quite sharp indicating an abrupt phase transition (APT) with a relatively large latent heat and the single phase nature of the material. 22 The latent heat peaks associated with the magnetoelastic transition in Ba 3 BiRu 2 O 9 and martensitic transformation in Mn-NiSn alloy, on the other hand, are relatively small. 27,28 The noise in the DTA peaks in Fig.…”
Section: A Dta Measurements and Extraction Of Latent Heatmentioning
confidence: 97%
See 1 more Smart Citation
“…5 (b)] are quite sharp indicating an abrupt phase transition (APT) with a relatively large latent heat and the single phase nature of the material. 22 The latent heat peaks associated with the magnetoelastic transition in Ba 3 BiRu 2 O 9 and martensitic transformation in Mn-NiSn alloy, on the other hand, are relatively small. 27,28 The noise in the DTA peaks in Fig.…”
Section: A Dta Measurements and Extraction Of Latent Heatmentioning
confidence: 97%
“…7, we had previously observed that the depth of supercooling and superheating increases with the temperature scan rate R, and follows a dynamical scaling relation ∆T (R) ∝ R Υ . 22 Here ∆T (R) = |T j 0 − T j R |, j = H, C, is the shift in the phase transition temperature to an R-dependent value T H R > T H 0 during heating and T C R < T C 0 during cooling. T H 0 and T C 0 are the transition temperature under a quasistatic change in the sample temperature under heating and cooling conditions respectively.…”
Section: B Latent Heat Of Supersaturated Transitionmentioning
confidence: 99%
“…Metal-insulator phase transitions in some materials, such as V 2 O 3 , were classified as zeroth-order phase transitions, where the free energy is discontinuous [21,22]. These phase transitions exhibit the phase coexistence and ramified fractal-like nanoscale phase separation in the transition region [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Metal-insulator phase transitions in some materials, such as V 2 O 3 , were classified as zerothorder phase transitions, where the free energy is discontinuous [21,22]. These phase transitions exhibit the phase coexistence and ramified fractal-like nanoscale phase separation in the transition region [21][22][23].…”
Section: Introductionmentioning
confidence: 99%